Developments in ore characterisation for coarse gangue rejection amenability - Agbenuvor, Bernard; Avelar, Erica; Teresa, McGrath; Aldrich, Chris (2021)
Coarse gangue rejection (CGR), a method utilized for ore upgrade by physical methods (screens and density) or sensor-based detection, has become highly topical in the modern mining value chain. However, selecting an ore suitable for such an approach has been the main setback for its more comprehensive application. Despite the advancement of technology, characterization for ores amenable to coarse gangue rejection is still limited, mainly in the gold sector. The current declining nature of ore grade and the emergence of complex ores have made ore characterization more critical. Currently, during deposit development and mining operation, ore characterization is an integral component of the process. It provides a great deal of information about an ore, contributing to overall process performance prediction and managing uncertainties in mineral processing plants. As for every other mineral processing unit operation, ore characterization for coarse gangue rejection helps understand the inherent properties of ore that influence the separability of the product stream. In light of this, this paper looks at a brief review of ore characterization methods that have been utilized in literature for identifying ores that are amenable for coarse gangue rejection and assesses the opportunities available for further improvement to the methodology. The advancement in geometallurgy has seen ore characterization shifting toward more comprehensive geometallurgical approaches. Identifying geometallurgical parameters indicating CGR performance before conducting complete CGR characterization is seen as a vital tool in driving future CGR characterization methods.